Performance evaluation of throated downdraft gasifier using peanut shell and mango seed hull as a feedstock - Behailu Ibrahim Ali; Dawit Gudeta Gunjo (Results in Engineering, 2023)
Bioenergy, or energy derived from biomass, has the potential to displace fossil fuels in the near future due to its abundance, cleanliness, and carbon dioxide neutrality. From biomass thermochemical treatments, the release of syngas, which can be employed in various heat and power generation systems, makes gasification particularly alluring. When a syngas with little tar and impurity is required most of the time downdraft gasifiers are among the first gasification systems that are chosen. The current study aims to investigate the performance of a throated downdraft gasification system by using a model and experiments based on the characterization of pretreated biomass feedstock. Mango seed hull (MSH) and peanut shell (PS), two biomass wastes that were readily available locally, were used for the analyses. The producer gas generated with MSH has a composition of 18.34 % H2, 23.87 % CO, 14.83 % CO2, and 1.27 % CH4 in a wet basis. The calorific value was determined to be 4.89 MJ/Nm3. Similarly, the PG was produced with 9 mm PS pellets and 17.93 % H2, 24.43 % CO, 12.47 % CO2, and 1.22 % CH4 in a wet basis. The calorific value was found to be 4.96 MJ/Nm3. From the model for MSH the syngas composition in wet basis was found to be 22.38 % H2, 24.16 % CO, 8.43 % CO2, 0.24 % CH4, which shows how close the prediction of the model and the experimental results are, which is also similar for the PS. When MSH and 9 mm PS pellets were utilized, gas with good flame characteristics was produced. Additionally, the gasifier's overall performance for these feedstocks was favorable. Thus, MSH and PS are discovered to be good biomass feedstocks for producing syngas through biomass gasification based on the model and the conducted experiments.